Gender and climate-resilient agriculture: A review of concepts and practical resources in support of gender-transformative change - Nelson, Valerie; Forsythe, L. (CGIAR GENDER Impact Platform, 2023)
To advance the use of gender-transformative approaches in climate-resilient agriculture (CRA), a review of practical resources that could support researchers and practitioners in applying gender and CRA was undertaken. The review consolidates and assesses diverse, practical resources—including research tools, methods and broader guidance—that aim to address gender inequalities/inequities, climate and agriculture, albeit to varying degrees. A conceptual framework was developed to guide the review, which helped to establish the gender dimensions of climate-resilience processes, and then to assess how the practical resources addressed these dimensions. The types of practical resources identified as critically important for climate resilience are as follows: (1) anticipatory, foresight and scenarios; (2) context and enabling environment; (3) causes and patterns of vulnerability and resilience; (4) CRA agricultural innovation systems; (5) CRA practices, technologies, innovations and services; (6) appraisal of specific CRA practices; (7) assessing CRA outcomes of processes and interventions; and (8) transformative change. In total, 44 practical resources were identified, of which 16 were identified as tools/ methods, and 28 as broader guidance documents (such as information notes). The review considers how gender and intersectionality are addressed in each practical resource, and the quality and ethical issues that may arise from using the resource. After mapping the existing resources, the review identified key gaps in the practical resources available. These gaps included: anticipatory and foresight resources, enabling environment to support gender and CRA, and analysis of gender and agricultural research and extension. A range of promising practical resources are identified that could be adapted to support gender-transformative approaches to CRA, from areas such as gender and value-chain analysis, gender-based violence, landscape approaches, migration, gender and social norms, and men and boys’ engagement.